Admissibility of the administrative process in the global order - Sesín, Domingo Juan (Universidad Nacional del Litoral, 2014)
From the incorporation of the international treaties constitutional texts-such as in our country through art. 75 paragraph 22 of the Constitution Nacional- both Articles 8 and 25 of the Pact of San José de Costa Rica and the remaining provisions constitute direct source application, and therefore has traditionally reinforced what we recognized as due process under the own national constitutions. In this context, we have tried to provide an overview of doctrinal and jurisprudential analysis of the different aspects and specific problems that relate to the admissibility of the administrative proceedings, which by its particularities have earned an adjusted treatment by local courts to achieve an adequate definition of its content and scope. To do this, we have examined the various procedural requirements related to administrative litigation and the main causes of admission and inadmissibility of special judicial process from analysis and study of specific real situations to provide guidance on the interpretation of objective law by the judges as a practical and concrete strategy for the various operators of law.